AC electrokinetic isolation and detection of extracellular vesicles from dental pulp stem cells: Theoretical simulation incorporating fluid mechanics. Issue 20 (8th June 2021) - Hadady, Hanieh; Karamali, Fereshteh; Ejeian, Fatemeh; Haghjooy Javanmard, Shaghayegh; Rafiee, Laleh; Nasr Esfahani, Mohammad Hossein
Abstract: Extracellular vesicles (EVs) are cell‐derived nanoscale vesicles involved in intracellular communication and the transportation of biomarkers. EVs released by mesenchymal stem cells have been recently reported to play a role in cell‐free therapy of many diseases. However, the demand for better research tools to replace the tedious conventional methods used to study EVs is getting stronger. EVs' manipulation using alternating current (AC) electrokinetic forces in a microfluidic device has appeared to be a reliable and sensitive diagnosis and trapping technique. Given that different AC electrokinetic forces may contribute to the overall motion of particles and fluids in a microfluidic device, EVs' electrokinetic trapping must be examined considering all dominant forces involved depending on the experimental conditions. In this paper, AC electrokinetic trapping of EVs using an interdigitated electrode arrays is investigated. A 2D numerical simulation incorporating the two significant AC electrokinetic phenomena (Dielectrophoresis and AC electroosmosis) has been performed. Theoretical predictions are then compared with experimental results and allow for a plausible explanation of observations inconsistent with DEP theory. It is demonstrated that the inconsistencies can be attributed to a significant extent to the contribution of the AC electroosmotic effect.